2023
DOI: 10.1111/bcpt.13874
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of older patients' willingness to have medications deprescribed: A cross‐sectional study

Abstract: BackgroundDeprescribing is a complex process requiring a patient‐centred approach. One frequently expressed deprescribing barrier is patients' attitudes and beliefs towards deprescribing. This study aimed to identify the predictors of patients' willingness to have medications deprescribed.MethodsA cross‐sectional study was conducted with community‐dwelling patients aged ≥65 who are taking at least one regular medication. Data collection included patients' demographic and clinical characteristics and the Portug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…Our findings indicate that the majority (90%) of patients were willing to be deprescribed. This is in line with previous studies that used the rPATD questionnaire, which reported that the majority of older patients 15 and patients with type 2 diabetes 16 were willing to deprescribe their medication. However, only 43% were satisfied with their prescribed medications, and previous studies have reported that willingness to be deprescribed was positively associated with satisfaction with current medications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings indicate that the majority (90%) of patients were willing to be deprescribed. This is in line with previous studies that used the rPATD questionnaire, which reported that the majority of older patients 15 and patients with type 2 diabetes 16 were willing to deprescribe their medication. However, only 43% were satisfied with their prescribed medications, and previous studies have reported that willingness to be deprescribed was positively associated with satisfaction with current medications.…”
Section: Discussionsupporting
confidence: 92%
“…A total of 242 patients were included in the analysis, consistent with sample sizes in other studies on the topic. 15 , 16 …”
Section: Methodsmentioning
confidence: 99%
“…Such concerns should thus be carefully considered when addressing deprescribing in this patient population. In fact, more concerns have been shown to decrease patients' willingness to try deprescribing 27 . Thus, developing a thorough understanding of patients' potential treatment scepticism, specific concerns and past experiences can potentially help health care professionals better support them throughout the deprescribing process, ultimately promoting a more patient‐centred approach that takes into account the needs and preferences of older patients with psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Lundby et al 18 report their results from the revised Patients' Attitudes Toward Deprescribing (rPATD) questionnaire administered in a geriatric psychiatry setting and describe willingness to deprescribing but also previous bad deprescribing experiences among patients. Pereira et al 19 present their results from the rPATD questionnaire to identify predictors of older community-dwelling patients' willingness to deprescribing, finding that older age and female sex increase the odds of willingness to deprescribing. Similarly, McCarthy et al 20 explore the relationship between patient attitudes and medication changes in older people using the rPATD and report that willingness to deprescribing is associated with higher rates of both stopping and starting medications.…”
mentioning
confidence: 99%